Regulation of Stemness by NR1D2 in Colorectal Cancer - Sandra Alonso-García; Paula Sánchez-Uceta; Sara Moreno-SanJuan; Jorge Casado; Jose D. Puentes-Pardo; Huda Khaldy; David Lopez-Pérez; María Sol Zurita-Saavedra; Cristina González-Puga; Angel Carazo; Josefa León (Biomedicines, 2025)
Background: Nuclear Receptor Subfamily 1 Group D Member 2 (NR1D2), a transcription factor that regulates the circadian clock, has been described as an oncogene in colorectal cancer (CRC). In several types of cancer, NR1D2 regulates cancer progression and relapse through cancer stem cells (CSCs), although this aspect has not been studied in CRC. On the other hand, p53 is a tumour suppressor gene that appears mutated in approximately a 50% CRCs. Interestingly, p53 is considered to be a crucial nexus between circadian clock deregulation and cancer. In addition, p53 regulates CSC phenotypes. Methods: We developed an in vitro model in which NR1D2 was silenced in three isogenic cell lines with different p53 status. In addition, we analysed the expression of NR1D2 in a cohort of patients and determined its relationship with the characteristics of patients and tumours. Results: In the in vitro model, NRID2 silencing reduces cell growth and decreases stemness, although only in cells harbouring a wild type p53. In contrast, in cells lacking a functional p53 or harbouring a mutated one, NR1D2 knockout increases cell growth and stemness. In patients, NR1D2 expression correlates with poorly differentiated tumours and high expression of CSCs markers, although only in tumours with a wild type p53, corroborating the results obtained in the in vitro model. Conclusions: Although more research is needed to analyse the mechanism by which NR1D2 regulates stemness in a p53-dependent manner, our results highlight the possibility of using NR1D2 antagonists for treating this type of patient and to develop personalised medicine.